Pengaruh pemberian kecambah kacang hijau (Phaseolus radiatus (L.)) terhadap kadar malondealdehid (MDA) plasma dan jaringan hati tikus Sprague Dawley yang diberi pakan lemak tinggi - Novidiyanto Novidiyanto; Arta Farmawati; Lily Arsanti Lestari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: High-fat diet increases the levels of fat, especially cholesterol and triglycerides that cause hyperlipidemia. Polyunsaturated fatty acids are very easily oxidized by free radicals reactive oxygens species (ROS) called lipid peroxidation, to produce compounds that malondialdehyde (MDA), is toxic and can damage plasma membrane and liver tissue. Mung bean sprouts are known to contain antioxidants which act to inhibit lipid peroxidation process.Objective: Determine the effect of mung bean sprouts to the level of plasma MDA and liver tissue of rats with high-fat diets.Method: This research is an experimental study with an only post-test design with the control group. Thirty-five male Sprague-Dawley rats were divided into 5 groups. Group K1 received fed standard; K2 received high-fat diet without mung bean sprouts. Group P1 received high-fat diet and mung bean sprouts dose of 0.5 mL/gBW. Group P2 received high-fat diet and mung bean sprouts dose of 1 mL/gBW. Group P3 received high-fat diet and vitamin E doses of 23 IU. All group were treated for 28 days. Analysis of MDA plasma and liver tissue performed after treatment.Results: Group K1 has plasma MDA levels of 1.17 ± 0.14 nmol/mL Mean MDA plasma level in the group K1 Group of K1 Mean MDA plasma level in the group K2 (39.7±0.19 nmol/mL) was higher than the group of K1 (1,17±0,14 nmol/mL), group P1 (2.94±0.09 nmol/mL), group P2 (1.73±0.08 nmol/mL) and group P3 (1.53±0.07 nmol/mL). Group K1 has liver tissue MDA Levels of 1,64±0,11 nmol/g. Mean MDA liver tissue level in the group of K2 (4.90±0.29 nmol/g) was higher than the group of P1 (3.68±0.45 nmol/g), group P2 (2.27±0.10 nmol/g), and group P3 (2.01±0.11 nmol/g).Conclusion: Level of MDA plasma and liver tissue of rat in group P1 and P2 was lower than a level of MDA plasma and liver tissue of rat in group K1, but higher than the level of MDA plasma and liver tissue of rat in group P3. There was a very strong correlation between the level of MDA plasma and liver tissue of rat was given the mung bean sprouts and high-fat diet.